Pulmonary tuberculosis and management of contact patients in a Department of Nephrology and Kidney Transplantation - Burguet, Laure; Duvignaud, Alexandre; Nguyen, Duc; Receveur, Marie-Catherine; Kaminski, Hannah; Pellegrin, Isabelle; Rogues, Anne-Marie; Peuchant, Olivia; Moreau, Karine; Merville, Pierre; Couzi, Lionel (International journal of infectious diseases, 2022)
•This study explored tuberculosis (TB): management of contact patients with kidney disease or transplant.•TB treatment was given to contacts of circle 1 or with positive IGRA.•No case of TB disease occurred in this cohort of immunocompromised patients.•Systematic TB prophylaxis on highly vulnerable contact is questionable. To describe the investigation, follow-up, management, and outcomes in a cohort of chronic kidney disease (CKD) and kidney transplant recipients (KTR) exposed to a case of pulmonary tuberculosis (TB). Contacts were investigated following a concentric circles approach and followed-up according to their level of priority. In those with evidence of latent TB infection, treatment decision was based on the level of exposure, individual vulnerability, as well as the results of an interferon-gamma release assay. A total of 130 patients with CKD and 180 KTR were identified as contacts and followed-up over a 2-year period. Few vulnerable high-priority contacts received anti-TB treatment, including the two (100%) highly exposed patients in circle 1, 11/78 (14.1%) CKD patients and 4/142 (2.8%) KTR in circle 2, and 10/52 (19.2%) CKD patients and 2/36 (5.6%) KTR in circle 3; all had a positive interferon-gamma release assay result. No incident cases of TB disease occurred. These findings suggest that latent TB treatment, as recommended in European guidelines, might be reasonably avoided in vulnerable high-priority contacts of circle 2, with a negative interferon-gamma release assay and in countries with low prevalence of TB.